Public private partnership monitor. (Public private partnership monitor., 2017)
The first edition of the Public Private Partnership (PPP) Monitor tracks the development of the PPP business environment as well as the challenges of doing PPPs in nine of the ADB developing member countries (DMCs): Bangladesh, the People Republic of China, India, Indonesia, Kazakhstan, Papua New Guinea, the Philippines, Thailand and VietNam. It is divided into four main categories: Regulatory Framework, Institutional Capacity for Implementation, PPP Market Maturity, and Financial Facilities. The PPP Monitor aims to increase the level and quality of private sector participation in infrastructure in the ADB DMCs by serving as an active platform for dialogue between the public and private sectors.